Strategies for risk management in urban–rural conflict: Two case studies of land acquisition in urbanising China. (January 2017) - Shan, Liping; Yu, Ann T.W.; Wu, Yuzhe
Abstract: Urban and rural environments show clear differences in morphology, production mode and culture. With rapid urbanisation, these differences have become a major cause of urban–rural conflict. One of the most significant challenges arises from land acquisition, particularly in China, where cities have experienced substantial growth in the 21st century. Different types of risk are associated with land acquisition conflict in different Chinese cities. In this study, two types of cities are discussed: those with a historically low level of development but recent rapid economic growth, such as Yueqing; and cities that have maintained a relatively high level of development and experienced stable growth, such as Jiaxing. Land acquisition conflict in these two representative cities is then analysed in terms of property rights, access to resources and development. Analysis is performed at the institutional level to provide more accurate insights into the dynamics of conflict. The findings of the study suggest that different risk-management strategies are used in the two kinds of city, and that conflict is more likely to occur in cities with historically weaker development, such as Yueqing. To avoid such conflict, systematic risk-management strategies should be established in these cities. Highlights: We study the key risk factors of China's urban-rural conflicts, particularly in land requisition. Two cases in China are used as the analysis objects to examine the proposed theory. Different key factors and strategies are studied in the different cases. Strategic solutions for risk management in Chinese urban-rural conflict are suggested.